PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN MODEL PEMBELAJARAN PAIKEM PADA SISWA KELAS SMA - Dinihari, Maria; Heryana, Nanang; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study provides an effort to create an effective and efficient teaching and learning process using the PAIKEM model (Active, Interactive, Creative, Effective, and Fun Learning) in learning poetry writing skills in class X MIA Sompak 1 High School. The problem in this research is how the process and results of learning to write poetry use the PAIKEM approach. Based on data analysis, this study produces a conclusion in the first cycle the results of the ability of students to write poetry using the PAIKEM model in class X MIA obtained an average score of 59,400% while in the second cycle the ability of students to write poetry using the PIKEM model in class X MIA obtained an average score of 69,750% , the increase that occurred from the learning process of writing poetry using the PAIKEM II cycle model was 76.66%. The results of this study are expected to be useful for students, teachers, students, and especially implementation in schools by increasing the integrity of Indonesian Language teacher workforce in Sompak 1 Public High School in delivering material to achieve the 2013 Curriculum learning objectives. Keywords: improvement, writing poetry, PAIKEM model